Therapeutic efficacy of direct oral anticoagulants and vitamin K antagonists for left ventricular thrombus: Systematic review and meta-analysis. - Tetsuji Kitano (Public Library of Science (PLoS), 2021)
Background Although several meta-analyses have compared efficacies of vitamin K antagonists (VKAs) and direct oral anticoagulants (DOACs) for treatment of left ventricular thrombus (LVT), those meta-analyses included no single-arm studies. Methods and results PubMed, Scopus, and the Cochrane Library databases were searched for articles investigating thrombus resolution, stroke, any thromboembolism, major bleeding, any bleeding, or all-cause death in LVT treated with VKAs or DOACs, and single-class meta-analyses were also included (PROSPERO database, CRD42021230849). Event rates were pooled using a random effects model. Meta-regression analysis was performed to explore factors that may influence outcomes. 2,612 patients from 23 articles were included (VKAs: 2,004, DOACs: 608). There were no significant differences between VKAs and DOACs in the frequency of thrombus resolution (VKAs: 0.75 [95% confidence interval; 0.67 to 0.81], DOACs: 0.75 [0.67 to 0.82]), stroke (VKAs: 0.06 [0.04 to 0.10], DOACs: 0.02 [0.01 to 0.01]), any thromboembolism (VKAs: 0.08 [0.05 to 0.13], DOACs: 0.03 [0.01 to 0.10]), major bleeding (VKAs: 0.06 [0.04 to 0.09], DOACs: 0.03 [0.01 to 0.06]), any bleeding (VKAs: 0.08 [0.05 to 0.12], DOACs: 0.08 [0.06 to 0.10]), and all-cause death (VKAs: 0.07 [0.04 to 0.13], DOACs: 0.09 [0.05 to 0.16]). Meta-regression analysis revealed that increased duration of follow-up was associated with lower-rates of stroke (estimate: -0.040, p = 0.0495) with VKAs, but not with DOACs. There was significant publication bias for thrombus resolution, stroke, any thromboembolism, any bleeding, and all-cause death. Conclusions Efficacy and adverse outcomes of therapy with DOACs and VKAs do not differ. Randomized controlled trials are needed to determine the optimal anticoagulant strategy.